“Suicide’s very abstract”: A qualitative analysis of risk assessment training recommendations from family physicians - Mark A. Dixon; Kathleen A. McNamara; David A. Moss (Qualitative Research in Medicine & Healthcare)
Suicide risk has consistently increased over the past 2.5 decades, despite growing awareness and tailored programs aimed at combating this epidemic. Suicide prevention initiatives include ensuring 24/7 access to crisis hotlines, encouraging individuals to seek mental health care, and reducing access to lethal means among high-risk populations. A recent area of focus is the physician’s office, as research shows that nearly half of those who die by suicide had seen a primary care physician within one month of their death. However, primary care physicians do not consistently inquire about suicide risk among their patients. This study presents findings from 15 interviews with family medicine residents at a U.S. military hospital. Participants identified gaps in three key areas of training: i) foundational knowledge (e.g., risk assessment flow, available tools and resources, and therapeutic skills), ii) training program structure (e.g., timing, exposure, and effectiveness), and iii) training culture (e.g., fostering courage and support). Residents recognized their central role in suicide prevention and were eager to address perceived gaps in their knowledge. They also shared their ideal training environment, which would support learning and skill development. This paper offers clear and actionable recommendations for family medicine residency programs to advance the suicide prevention agenda.